Pengembangan Media Pembelajaran Menggunakan Adobe Flash Pada Mata Kuliah Kelistrikan Otomotif - Yudistira Gustianto; Agus Dudung; Ratu Amilia Avianti (Risenologi, 2021)
Adobe Flash is a comprehensive animation creation program that makes it easy for developers to create animations. Animation is a series of accurately processed images that directly produce memorable movements with sound and store a learning message. This study aims to develop learning media using Adobe Flash in automotive electrical courses. Based on the results of a survey of learning media needs analysis to students of Mechanical Engineering Education, State University of Jakarta whose data was collected using Google Form, 80% of respondents answered that the media most often used in Automotive Electrical courses was Power Point. 93.3% of respondents answered the need to develop android application-based learning media for Automotive Electrical courses. Research and Development research methods and ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) are used in this study. Place of research at the State University of Jakarta for students who have completed and are taking Automotive Electrical courses. The method of data collection is a questionnaire to test the feasibility of the media. Based on the eligibility criteria by Arikunto, the validation test by material experts stated that the learning media tested obtained the "very feasible" criteria with a percentage value of 85.33%. Furthermore, the validation test by media experts stated that the learning media tested obtained the "very feasible" criteria with a percentage value of 81.33%. And the results of small group trials to 7 students get a percentage of 90.28% which is in the "very feasible" interval. While the results of field trials to 20 students get a percentage of 90.4% which is in the "very feasible" interval. Based on the data above, it can be concluded that the media developed is very feasible and can be used in learning.